Adaptive large neighborhood search for vehicle routing problems with transshipment facilities arising in city logistics. (January 2022) - Friedrich, Christian; Elbert, Ralf
Abstract: In this paper, we investigate vehicle routing problems with third-party transshipment facilities that arise in the context of city logistics. Contrary to classical vehicle routing problems, where each customer request is delivered directly to its destination, the problems considered in this paper feature the alternative possibility of delivering customer requests to third-party transshipment facilities, such as urban consolidation centers, for a fee. We present an adaptive large neighborhood search with an embedded random variable neighborhood descent as a local search component and a set-partitioning problem for the recombination of routes to solve various versions of the problem. Thereby, we consider location-dependent time windows as well as heterogeneous fleets and propose several new procedures that consider transshipment facilities within the components of our adaptive large neighborhood search. The proposed method is tested on benchmark instances from the literature as well as newly created benchmark instances. It shows promising results, leading to multiple improvements over existing algorithms from the literature. Moreover, a real-world study is presented to gain managerial insights on the impact of transshipment fees, order size, and heterogeneous fleets on the transshipment decisions. Highlights: Extends the vehicle routing problem with transshipment facilities by introducing time windows and heterogeneous fleets. Presents an adaptive large neighborhood search (ALNS) for vehicle routing problems with transshipment facilities. Tests the ALNS on benchmark instances for problems from the literature. Analyzes factors impacting the transshipment facility usage through a real-world study.